Sonographic Imaging and Cytological Changes in Thyroid in Patients with Breast Carcinoma - Shrestha, Manisha; Paruliya, Dipak; Kuma, Anand (Journal of Universal College of Medical Sciences, 2018)
Introduction: The association between thyroid disorders and breast cancer is debated. A possible relationship between breast carcinoma and thyroid disorders have been suggested considering the fact that the breast malignancy may alter endocrine homeostasis. A prospective cross sectional study in breast cancer patients was performed to evaluate the association of breast cancer with thyroid disorders. Ultrasonography and cytological changes in thyroid gland were evaluated. Materials and methods: The study included 30 consecutive newly diagnosed breast cancer patients between the age group of 30 to 60 years. The study had a control group of 20 age matched patients from the same geographical area with no breast or thyroid disease and no malignancy. The presence of thyroid disease was examined by using well defined diagnostic criteria of ultrasonography. The observations on ultrasound were correlated with cytological assessment in breast cancer patients only. Results: Results were analyzed statistically by Fischer's exact probability test, Pearson correlation coefficient and unpaired student 'T' test. Sonographically nodular thyroid was observed in 50% of breast cancer patients as compared to 10% in control group (p<0.002). Majority of patients had solitary and solid echo texture thyroid nodules. There was a direct correlation between the stage of breast cancer and total thyroid volume. All thyroid nodules were cytologically benign (adenomatous/ colloid nodular goiter) on cytological evaluation. Conclusion: It is concluded that an increased preponderance of thyroid disorders exist in patients with breast cancer.